KERENTANAN SISWA MELAKUKAN KEKERASAN MASSA LATAR BELAKANG DAN UPAYA PENANGGULANGANNYA - DYP Sugiharto (Jurnal Cakrawala Pendidikan, 2003)
Student's collective violence may be caused by moral crisis. Over sensitivity and reactive also caused ofsensitivity student's collective violence. Based on those problems the research was executed. Meanwhile, the goals of research are to investigate the factors that caused the sensitivity of student's violence, to describe the group and collective violence form, and to handle the student's collective violence. The sample consisted of 118 students from higher school at Semarang city that chosen by cluster-proportional random sampling technique. The data wer..t collected by questionare and indept interview. The data collected were analized bypercentage and mode. The findings reveal that (l) the sensitivity ofstudent's collective violence caused by limitedness to hold-the spirit oflive; emotional disposition; frustation; a narrowminded viewpoint; (2) the goups and forms ofstudent's violence are cruel treatment, be contrary to rule; helping the goals oforganization and those violence are exeuted throught individual and collective can be handled throught pre-emtive